Implementasi Kurikulum Berbasis Industri melalui Pendekatan Pembelajaran Sistem Blok pada Mata Pelajaran PPKn di SMK Ma’arif Salam - Dennis Fella Febrina; Elsa Putri Ermisah Syafril (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to get an overview of the industry-based curriculum implementation which is carried out through a block system learning approach in Civics subjects at Ma'arif Salam Vocational School. This research was carried out using a qualitative method based on various findings, processes, and results related to the implementation of an industry-based curriculum through a block system learning approach in Civics Education subjects. Based on the analysis of the existing data, it was found that the curriculum used was the 2013 curriculum with a model centered on project-based learning (Project Based Learning), problem-based learning models (Problem Based Learning), and discovery learning models. In addition, it was also found that the learning process at SMK Ma'arif Salam has used a block system which is done by grouping effective study hours into one unit of time with reference to a dual base program in order to reflect the culture of work patterns from industry intensively. Of course, there are various challenges and obstacles in implementing an industry-based curriculum with block system learning in PPKn subjects at SMK Ma'arif Salam, such as the lack of focus on the development and implementation of PPKn learning compared to other lessons, school orientation which is more focused on student graduation than distribution. work in industry, as well as mental blocks from the school will change.